Effects of Aligning Residency Note Templates with CMS Evaluation and Management Documentation Requirements - Stern, Sarah; Lippert, William C.; Rigdon, Joseph; Obermiller, Corey; Witek, Lauren; Anderson, Matthew; Chebrolu, Sneha; Moses, Adam; Xiao, Ted; Dharod, Ajay; Cristiano, Joseph A. (Applied Clinical Informatics, 2025)
Background The Centers for Medicare & Medicaid Services (CMS) introduced changes in outpatient and inpatient evaluation and management (E/M) current procedural terminology (CPT) codes in 2021 and 2023, which were intended to streamline providers' clinical documentation.Objectives This experiment aimed to study the effects of aligning inpatient and outpatient note templates with updated CMS guidelines on character length and documentation time per note at an internal medicine residency program in the southeastern United States.Methods In April 2023, the Atrium Health Wake Forest Baptist Internal Medicine Residency Program's inpatient and outpatient note templates were updated according to the most recent CMS guidelines. A pre–post analysis of resident documentation time and length was conducted comparing notes written with the residency note templates from May 1, 2022, to August 31, 2022 (6,439 notes) to notes written with the residency note templates from May 1, 2023 to August 31, 2023 (8,828 notes). Interns were surveyed regarding their perceptions of the updated note templates.Results After the note template updates, on adjusting for differing percentages of note types in the pre- and postperiods and accounting for multiple notes written by each resident, notes written with the residency note templates decreased by a mean character length of −882 characters (95% CI: −953, −811, p < 0.0001), while time spent writing notes did not significantly decrease. 17/17 respondents had favorable perceptions of the note templates.Conclusion The internal medicine residency inpatient and outpatient note templates were updated to align with the most recent CMS E/M documentation requirement changes. These note template changes were associated with a meaningful decrease in documentation length but no overall significant reduction in mean documentation time when adjusted for differing percentages of note types in the pre- and postperoids and multiple notes written by the same author. The interns perceived the note template changes positively.
Keywords: encounter notes; documentation burden; notes; electronic health records and systems; efficiency improvement